Employee Social Network Strategies: Implications for Firm Strategies and Performance in Future Organizations - Thiel, Monica (Frontiers in Psychology, 2021)
Employee social network strategies play a key role in firm strategies and organizational performance. Currently, scholars underestimate the contributions of employee social strategies in firm strategies. Little is known how informal employee social networks, group entitativity and competition could shape and direct firm strategies and organizational performance. The article examines social network theory and strategic management’s content, process and open schools of thought to propose a new interpretation for managing firm strategies. More specifically, the author examines alternate causal paths, underlying processes and structures as mechanisms in employee social network strategies within a theoretical framework. The article proposes 4 theoretically driven propositions and makes two contributions. First, the article contributes to organizational behavior literature by focusing on the literature gap in network dynamics and competitive actions through employee social networks. Second, although there is immense literature on positive and negative employee competition in business, the article makes a contribution to the strategic management literature by moving beyond formalized structures and roles within an organization to focus on the multilevel informal workplace social interactions and processes that impact strategizing activities. Overall, the article extends strategy research in relation to how employee social networks operate through competition and group entitativity in firm strategies.